Understanding ecohydrology and biodiversity in aquatic nature-based solutions in urban streams and ponds through an integrative multi-tracer approach - M. M. Warter; D. Tetzlaff; D. Tetzlaff; D. Tetzlaff; C. Soulsby; C. Soulsby; C. Soulsby; T. Goldhammer; D. Gebler; K. Vierikko; M. T. Monaghan; M. T. Monaghan (Hydrology and Earth System Sciences)
Rapid urbanization and climate change affect ecohydrology, biodiversity, and water quality in urban freshwaters. Aquatic nature-based solutions (aquaNBSs) are being widely implemented to address some of the ecological and hydrological challenges that threaten urban biodiversity and water security. However, there is still a lack of process-based evidence of ecohydrological interactions in urban aquaNBSs and their relationship to water quality and quantity issues at the ecosystem level. Through a novel, integrative multi-tracer approach using stable water isotopes, hydrochemistry, and environmental DNA we sought to disentangle the effects of urbanization and hydroclimate on ecohydrological dynamics in urban aquaNBSs and understand ecohydrological functioning and the future resilience of urban freshwaters. Stable isotopes and microbial data reflected a strong influence of urban water sources (i.e., treated effluent, urban surface runoff) across stream NBSs. The results show potential limitations of aquaNBS impacts on water quality and biodiversity in effluent-impacted streams, as microbial signatures are biased towards potentially pathogenic bacteria. Urban ponds appear to be more sensitive to hydroclimate perturbations, resulting in increased microbial turnover and lower microbial diversity than expected. Furthermore, assessment of macrophytes revealed low diversity and richness of aquatic plants in both urban streams and ponds, further challenging the effectiveness of NBSs in contributing to aquatic diversity. This also demonstrates the need to adequately consider aquatic organisms in planned restoration projects, particularly those implemented in urban ecosystems, in terms of habitat requirements. Our findings emphasize the utility of integrated tracer approaches to explore the interface between ecology and hydrology and provide insights into the ecohydrologic functioning of aquaNBSs and their potential limitations. We illustrate the benefit of coupling ecological and hydrological perspectives to support future NBS design and applications that consider the interactions between water and the ecosystem more effectively.